2021
DOI: 10.1128/mbio.03134-21
|View full text |Cite
|
Sign up to set email alerts
|

Advances on the Role and Applications of Interleukin-1 in Tuberculosis

Abstract: Interleukin-1 (IL-1) is a key player in the immune response to pathogens due to its role in promoting inflammation and recruiting immune cells to the site of infection. In tuberculosis (TB), tight regulation of IL-1 responses is critical to ensure host resistance to infection while preventing immune pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 113 publications
(191 reference statements)
0
12
0
3
Order By: Relevance
“…Here, we have revealed that meropenem induces an exacerbated IL-1β secretion by Mtb -infected THP-1 macrophages. This finding should be further explored since host-directed therapies that modulate this cytokine may influence TB progression (67,68). Overall, our outputs contribute to clarifying the placement of beta-lactams in alternative regimens against Mtb , in alignment with WHO requirements for this class (9).…”
Section: Discussionmentioning
confidence: 96%
“…Here, we have revealed that meropenem induces an exacerbated IL-1β secretion by Mtb -infected THP-1 macrophages. This finding should be further explored since host-directed therapies that modulate this cytokine may influence TB progression (67,68). Overall, our outputs contribute to clarifying the placement of beta-lactams in alternative regimens against Mtb , in alignment with WHO requirements for this class (9).…”
Section: Discussionmentioning
confidence: 96%
“…Mtb infection upregulated MFN2 expression to enhance NLRP3 inflammasome formation (Xu et al, 2020). IL-1 is a key cytokine in the immune response against TB (Silveŕio et al, 2021). However, there is still curiosity about how Mtb actually induces inflammation.…”
Section: Inflammasome Activationmentioning
confidence: 99%
“…of IL-1R signaling leads to expansion of pathologic lesions in the lung [79][80][81][82][83][84] . We observed that in the absence of IL-1R, mice failed to form organized intestinal pyogranulomas and had elevated intestinal Yp burdens, corroborating previous reports that IL-1R signaling promotes anti-Yersinia defense 48,65,66 .…”
Section: Il-1r Signaling Is Critical For Infection Control During Tub...mentioning
confidence: 99%